Mass measurements of neutron-rich indium isotopes toward the N = 82 shell closure - Babcock, C.; Klawitter, Renee; Leistenschneider, E.; Lascar, D.; Barquest, B. R.; Finlay, A.; Foster, M.; Gallant, Aaron; Hunt, P.; Kootte, B.; Lan, Y.; Paul, Stefan Felix; et al. (Physical review. C, Nuclear physics, 2018)
Precise mass measurements of the neutron-rich 125-130In isotopes have been performed with the TITAN Penning trap mass spectrometer. TITAN's electron beam ion trap was used to charge breed the ions to charge state q=13+ thus providing the necessary resolving power to measure not only the ground states but also isomeric states at each mass number. In this paper, the properties of the ground states are investigated through a series of mass differentials, highlighting trends in the indium isotopic chain as compared to its proton-magic neighbor, tin (Z=50). In addition, the energies of the indium isomers are presented. The (8−) level in 128In is found to be 78 keV lower than previously thought and the (21/2−) isomer in 127In is shown to be lower than the literature value by more than 150 keV.
Gesehen am 22.06.2020